Kajian SCL, CL dan CBL terhadap Pemahaman Mahasiswa dalam Pembelajaran Statistik - Eliza, Eliza (Jurusan PIPS FKIP UMMY Solok, 2018)
The development of the era that is accompanied also by the progress of technology becomes a benchmark to realize the quality of the education system is increasing. The commitment and necessity in improving the quality of education is very important, especially to overcome the phenomenon of the decrease of the quality of education itself which can be seen from the past learning method, where the students only listen to the material explanation from the lecturer and only to understand the lecturer's explanation and make notes. In this era of globalization and technological advancement so fast and sophisticated as it is today that information and knowledge spread quickly and cheaply. This causes everyone to access information and learn knowledge in an easy way. HEALTS issued by the Director General of Higher Education provides a mandate, one of which is the application of SCL principles in the learning process. There are various learning methods for SCL, two of which are CBL and CL. The purpose of this study is to further examine the effect of SCL, CL, and CBL on student understanding in statistical learning. The population of this research is UPI YPTK students with purposive sampling sampling technique. The method of analysis of this study using multiple linear regression analysis. Based on the results obtained, that SCL and CBL have no significant influence, whereas CL has a significant influence on students' understanding in statistical learning. In the future, SCL and CBL methods can contribute greatly in learning especially to students.